2020
DOI: 10.35808/ersj/1682
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Subannual Seasonality of Building Construction in European Countries

Abstract: Purpose: The objective of this study involves the determination of cyclical characteristics that occur on the European construction market. Design/Methodology/Approach: In the research implementation process, time-frequency analysis was used to identify and analyze cyclicalities in the construction market. Findings: The results clearly demonstrate the absence of a homogeneous construction market in the investigated countries. The diversity of the European construction market is revealed by the various response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…2, a similar pattern of variability in the number of people injured in occupational accidents in the construction industry is repeated, which proves the seasonal and cyclical nature of this phenomenon. Similar conclusions with regards to seasonality in the construction industry were formulated by Mach et al in [18]. In long-term studies concerning accident rates in many European and world countries, the formation of long-term trends in accident rates can be noticed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2, a similar pattern of variability in the number of people injured in occupational accidents in the construction industry is repeated, which proves the seasonal and cyclical nature of this phenomenon. Similar conclusions with regards to seasonality in the construction industry were formulated by Mach et al in [18]. In long-term studies concerning accident rates in many European and world countries, the formation of long-term trends in accident rates can be noticed.…”
Section: Discussionsupporting
confidence: 81%
“…Seasonal factors affect the amount of construction production, which in turn affects the accidentality rate. Mach et al [18] identified cyclical fluctuations in relation to the construction industry in 16 European countries. Moreover, the authors of article [19] showed the dependence between the number of accident and production cycles in the construction industry in South Korea.…”
Section: Literature Surveymentioning
confidence: 99%
“…The analysis of this chart also indicates more regularities due to the seasonality of construction production rather than the effect of the constraints caused by the pandemic: a fall in the number of construction launches at the turn of the year, followed by an increase in the following spring. Some disruption is apparent just after the declaration of the epidemic threat, but the situation then normalises [32]. The seasonality of the construction industry is a well-known phenomenon that affects the volume of production [33].…”
Section: Changes In Housing Market In Poland During the Covid-19 Pand...mentioning
confidence: 99%
“…At the same time, there is a great need to predict the actual situation in this market and to make predictions over different time horizons for its key components. Thus, it is crucial to utilize effective predictive tools and constantly enhance existing ones, considering the unique features of the real estate market and the recurring emergence of abnormal situations, such as pandemics or armed conflicts (Hozer et al 2019;Kokot 2022;Mach 2019;Mach et al 2020). The real estate market has seen a successful implementation of predictive techniques utilizing artificial intelligence, including neural networks and linear regression (Huang et al 2011;Lin et al 2021).…”
Section: Introductionmentioning
confidence: 99%